STUDI LITERATUR: PENGARUH LATIHAN FISIK TERHADAP PENURUNAN KECEMASAN PADA LANSIA - Sakina Auliya Tehuayo; Marice Benga Olla; Saidah Rauf (Jurnal Keperawatan Indonesia Timur (East Indonesian Nursing Journal), 2021)
Background: Anxiety is the most frequently encountered mental health disorder, even among the elderly. Persistent anxiety in the elderly can impair their capacity to do daily tasks and diminish their sense of well-being. One of the recommended strategies for overcoming anxiety in the elderly is to engage in regular and quantifiable physical activity. Objective: To conduct a literature review to determine the effect of exercise on reducing anxiety in the elderly. Method: A literature review is a form of research that is conducted in this manner. Two databases, Pubmed and Google Scholar, were used to choose the papers. Prisma Flow is used to identify publications that are appropriate for repository use. After articles are filtered by keywords, they are verified for duplication across the two databases. The study publications used quasi-experimental and Randomized Control Trial (RCT) methods, were available in their entirety, and were published within the last decade. Additionally, the article used 45-year-old participants who had anxiety alone or in conjunction with other health conditions. Result: A total of ten articles were chosen. The ten articles used a variety of different forms of physical activity and anxiety measurement techniques. Each of these studies demonstrated a significant benefit of physical exercise in reducing anxiety in the elderly. Conclusion: Exercises such as gymnastics, walking, yoga, and breathing exercises have been demonstrated to be useful in lowering anxiety in the elderly. Keywords: Exercise; Anxiety; Elderly